Adaptação transcultural e percepção de usabilidade do leisure functional rehabilitation activity manual para o português brasileiro - Hausen, Daiane Oliveira (2022)
Rehabilitation from leisure activities is beneficial for neurofunctional stimulation of individuals who have suffered brain damage. In Brazil, there is a shortage of systematic protocols for the rehabilitation of patients with brain injury, thus, the cross-cultural adaptation of instruments with scientifically proven effectiveness, especially considering leisure activities of daily living. This research aimed to cross-culturally adapt the Leisure Functional Rehabilitation Activity Manual to Portuguese. The present study resulted in two academic products: 1) Cross-cultural adaptation and usability evidence of the Leisure Functional Rehabilitation Activity Manual into Brazilian Portuguese, through a combination of mixed method, composed of five experts in the field of rehabilitation to evaluate the material developed, linguistic and semantic equivalence with two professionals evaluating the idiomatic aspect of the adaptation; 2) Leisure Functional Rehabilitation Activity technical manual that was evaluated by 19 health professionals, including psychology, physiotherapy, medicine, nutrition, nursing, physical education, pharmacy, speech therapy, considering its usability of application and degree of difficulty. The data found emphasize the importance of the material in clinical practice, openness to innovation and adaptation of activities through the professional's expertise and an adequate systematization of activities. It is expected that the development of this material will contribute to the neurofunctional rehabilitation process and to the quality of life of adults and the elderly affected by neurological diseases/conditions, offering the option of a rehabilitation material adapted and carried out with scientific rigor for Portuguese Brazilian. However, it is suggested that further studies be carried out to test the effectiveness of activities in rehabilitation with the patient and that the domains of distributed leisure activities can continue to be investigated.